2008 IEEE International Electron Devices Meeting 2008
DOI: 10.1109/iedm.2008.4796744
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic modeling of impurity ion implantation in ultra-thin-body Si devices

Abstract: Source/drain formation in ultra-thin body devices by conventional ion implantation is analyzed using atomistic simulation. Dopant retention is dramatically reduced by backscattering for low-energy and low-tilt angles, and by transmission for high angles. For the first time, Molecular Dynamics and Kinetic Monte Carlo simulations, encompassing the entire Si body, are applied in order to predict damage during implant and subsequent recovery during anneal. These show that amorphization should be avoided as recryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 7 publications
3
16
0
1
Order By: Relevance
“…13,14 In a previous work, we showed that the atomistic simulation technique known as MD was able to reproduce the features observed in experiments. 15 These results were recently confirmed by other authors also using MD techniques. 16 This defected regrowth of narrow fin structures has even been modeled in a kinetic Monte Carlo code.…”
Section: Introductionsupporting
confidence: 80%
“…13,14 In a previous work, we showed that the atomistic simulation technique known as MD was able to reproduce the features observed in experiments. 15 These results were recently confirmed by other authors also using MD techniques. 16 This defected regrowth of narrow fin structures has even been modeled in a kinetic Monte Carlo code.…”
Section: Introductionsupporting
confidence: 80%
“…Figure 21(a) summarizes the dependence of dopant retention on implant conditions, as predicted by BCA calculations [153]. The incorporation of dopants in the sidewall of the fin improves as tilt implant angle increases (due to the reduction of backscattering), but high implant angles are not allowed in dense fin arrays.…”
Section: Dopant Incorporation Efficiencymentioning
confidence: 97%
“…Classical standard doping techniques like ion implantation may not be suitable for FinFET devices because of the 3D geometry. Several solutions to incorporate dopants in the fin are being explored such as tilted ion implantation [23,153,158], plasma doping [159][160][161][162] or vapor phase doping [163]. Among them, tilted ion implantation remains a strong candidate to introduce dopants into the fin, as it is a conventional and well established technique, although it suffers from specific issues that arise from the particular geometry of these devices.…”
Section: Doping Issues In Finfet Devices: a Challenge In 3dmentioning
confidence: 99%
See 1 more Smart Citation
“…The opposite of this is heating the wafer during implantation, as a method to promote dynamic annealing and thus the suppression of amorphisation. There have been a number of publications in this field for Si recently [81,82]. The drawback is that a special hard mask must be used, as the temperatures required to stifle amorphisation are higher than what photoresist can tolerate.…”
Section: Access Resistance 51 Doping Optimisationmentioning
confidence: 99%